w x y z = = = = a 4 + b 4 + c 4 + d 4 a 2 + b 2 + c 2 + d 2 a b + a c + a d + b c + b d + c d a b c d
Let a , b , c and d be real numbers; and w , x , y and z some unknown constants such that they satisfy the system of equations above. State the following expression
( a + b + c + d ) ( a 3 + b 3 + c 3 + d 3 + a b c + a b d + b c d + a c d )
in terms of w , x , y and z .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice question !!
I must admit that I considered against solving this question when I first saw it , but once you open it up and re-arrange it, this question's easy .
Or just call it newtons sums :)
For a shorter method try putting x = y = z = constant .
For example if we try x = y = z = 2 then only one options satisfiesand that is our answer
Log in to reply
Even better if you put a = b = c = d = 1
Only one option satisfies this. This is what i call Objective Approach
Using Newton's sum, we have:
a 4 + b 4 + c 4 + d 4 ⇒ w = ( a + b + c + d ) ( a 3 + b 3 + c 3 + d 3 ) − ( a b + a c + a d + b c + b d + c d ) ( a 2 + b 2 + c 2 + d 2 ) + ( a b c + a b d + a c d + b c d ) ( a + b + c + d ) − 4 a b c d = ( a + b + c + d ) ( a 3 + b 3 + c 3 + d 3 ) − y x + ( a b c + a b d + a c d + b c d ) ( a + b + c + d ) − 4 z
⇒ ( a + b + c + d ) ( a 3 + b 3 + c 3 + d 3 + a b c + a b d + a c d + b c d ) = w + x y + 4 z
Yes. This is the standard Newton's Sum approach. Well done!
Let a n + b n + c n + d n = P n , a + b + c + d = S 1 , a b + a c + a d + b c + b d + c d = S 2 , a b c + a b d + a c d + b c d = S 3 and a b c d = S 4 . By Newton's Sums we know that:
P 1 = S 1 P 2 = S 1 2 − 2 S 2 P 3 = S 1 3 − 3 S 1 S 2 + 3 S 3 P 4 = S 1 4 − 4 S 1 2 S 2 + 4 S 1 S 3 + 2 S 2 2 − 4 S 4
Then let A the expression that we want, that is A = S 1 ( P 3 + S 3 ) . Substituting the values obtained we obtain: A = S 1 ( S 1 3 − 3 S 1 S 2 + 3 S 3 + S 3 ) = S 1 4 − 3 S 1 2 S 2 + 4 S 1 S 3 .
Now, substituting the given values we obtain:
x = S 1 2 − 2 y w = S 1 4 − 4 S 1 2 y + 4 S 1 S 3 + 2 y 2 − 4 z A = S 1 4 − 3 S 1 2 y + 4 S 1 S 3
Now, subtract the third equation with the second one:
A − w = S 1 2 y − 2 y 2 + 4 z
Factor some terms and substitute the first equation:
A − w = y ( S 1 2 − 2 y ) + 4 z A − w = y ( x ) + 4 z
Finally, solve for A :
A = w + x y + 4 z
Thanks for deriving the formula!
Problem Loading...
Note Loading...
Set Loading...
First let us get acquainted to this identity.
a 4 + b 4 + c 4 + d 4 + ( a 2 + b 2 + c 2 + d 2 ) ( a b + a c + a d + b c + b d + c d ) + 4 a b c d = ( a + b + c + d ) ( a 3 + b 3 + c 3 + d 3 + a b c + a b d + b c d + a c d )
Now just substitute the values of w,x,y and z to get the answer.
Now, how is this identity derived? Don't worry it's derivation is not as lengthy as the identity. Let p(x) be a biquadratic polynomial with a roots a,b,c and d
∴ p ( x ) = x 4 − ( a + b + c + d ) x 3 + ( a b + a c + a d + b c + b d + c d ) x 2 − ( a b c + a b d + b c d + a c d ) x + a b c d
∴ p ( a ) = a 4 − ( a + b + c + d ) a 3 + ( a b + a c + a d + b c + b d + c d ) a 2 − ( a b c + a b d + b c d + a c d ) a + a b c d = 0
∴ p ( b ) = b 4 − ( a + b + c + d ) b 3 + ( a b + a c + a d + b c + b d + c d ) b 2 − ( a b c + a b d + b c d + a c d ) b + a b c d = 0
∴ p ( c ) = c 4 − ( a + b + c + d ) c 3 + ( a b + a c + a d + b c + b d + c d ) c 2 − ( a b c + a b d + b c d + a c d ) c + a b c d = 0
∴ p ( d ) = d 4 − ( a + b + c + d ) d 3 + ( a b + a c + a d + b c + b d + c d ) d 2 − ( a b c + a b d + b c d + a c d ) d + a b c d = 0
adding all the results yields the above identity.